Geopolitical Explanation of the State Department\'s Performance in Iran\'s Power Relations with Foreign Governments (1821-1847 M) - amin jairan; foead purarian (تحقیقات کاربردی علوم جغرافیایی)
The Qajar government in Iran was based on the geopolitical conditions of the expansionism of the European states, including Russia, Britain and France in the Middle East. On the other hand, the geopolitical position of Iran in the issues and interests of the regional powers of the great powers, brought about the importance and attention to the court of Iran, and this geopolitical attention and importance was the basis of Iran's foreign relations with superpowers of time. On this basis, the Iranian government established a network of ministries to handle foreign affairs. Thus, the analysis of the Ministry of Foreign Affairs' performance in Iran's political relations with foreign governments between the years (1200-1226), which reflects the geopolitical conditions of Iran during that period in the region and the international environment, can for the date Institutes and geopolitics can be solved. In this regard, this research is explained in a descriptive-analytical manner and its data and information are based on documents, manuscripts and library resources. The results of the research indicate that the foreign minister, as a manifestation of the State Department, in this historical period, while acknowledging the fact that Iran's geopolitical position in the region and international order has entered into its superficial duties, is due to the influence of other elements of power In the large-scale foreign decision-making, the role of the ceremonial role with its limited powers is diminished. But although the State Department was not able to decide independently of the other pillars of power, it was the ambassadors of this period who, by understanding the geopolitical position of Iran and the global conditions that could conceal the weak diplomacy of the Qajar apparatus and fill the vacuum of Iran's foreign policy apparatus.